Changes in Faecal Microbiota Profiles Associated With Performance and Birthweight of Piglets - Gaukroger, Clare H.; Stewart, Christopher J.; Edwards, Sandra A.; Walshaw, John; Adams, Ian P.; Kyriazakis, Ilias (Frontiers in Microbiology, 2020)
The gastrointestinal tract microbiota interacts with the host to modulate metabolic phenotype. The interaction could thus provide insights into why some low birthweight pigs can exhibit compensatory growth whilst others remain stunted. The study aimed to identify microbiota markers associated with birthweight (low birthweight (n = 13) or normal birthweight pigs (n = 13)) and performance (“good” or “poor” average daily gain class). Furthermore, the study determined whether the taxonomic markers were longitudinal, or time point specific in their ability to identify low birthweight pigs who could exhibit compensatory growth. Faecal samples were collected and liveweight recorded at 10 different time points from birth to 56 days of age. No consistent associations between birthweight, performance and gut microbiota were found across all time points. However, there was a significant (P < 0.05) effect of birthweight on microbiota richness at 21, 27, 32 and 56 days of age. Significant differences (P < 0.05) in genera abundance according to birthweight and performance were also identified. Low birthweight pigs had a significantly (P < 0.05) lower abundance of Ruminococcaceae_UCG-005, but a significantly (P < 0.05) higher abundance of Ruminococcaceae UCG-014 on days 21 and 32, respectively. Piglets classified as having a “good” average daily gain class had a significantly (P < 0.05) higher abundance of Lactobacillus, unclassified Prevotellaceae and Ruminococcaceae UCG-005 on days 4, 8 and 14, respectively. Furthermore, Ruminococcaceae UCG-005 was significantly more abundant at 14 days of age in normal birthweight pigs with a “good” average daily gain class compared to those classified as “poor”. The results of this study indicate that there are time point-specific differences in the microbiota associated with birthweight and performance, corresponding to the period in which solid feed intake first occurs. Identifying early-life microbiota markers associated with performance emphasises the importance of the neonatal phase when considering intervention strategies aimed at promoting performance.